2009
DOI: 10.5117/9789087280727
|View full text |Cite
|
Sign up to set email alerts
|

Sowing the seed? : Human Impact and Plant Subsistence in Dutch Wetlands During the Late Mesolithic and Early and Middle Neolithic (5500-3400 cal BC)

Abstract: In 2006 Leiden University has initiated a series Leiden Dissertations at Leiden University Press. This series affords an opportunity to those who have recently obtained their doctorate to publish the results of their doctoral research so as to ensure a wide distribution among colleagues and the interested public. The dissertations will become available both in printed and in digital versions. Books from this LUP series can be ordered through www.lup.nl. The large majority of Leiden dissertations from 2005 onwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…The real role of gathered plants we can estimate best when looking at spectra from waterlogged cultural layers. There we observe an increased diversity not only of gathered plants but also of weeds and other remains of the surrounding vegetation (Willerding 1971(Willerding , 1991Out 2009;Kroll 1981Kroll , 2007Jacomet, in press).…”
Section: Upgrading the Current State Of Knowledge Of Neolithic Crop Gmentioning
confidence: 91%
See 1 more Smart Citation
“…The real role of gathered plants we can estimate best when looking at spectra from waterlogged cultural layers. There we observe an increased diversity not only of gathered plants but also of weeds and other remains of the surrounding vegetation (Willerding 1971(Willerding , 1991Out 2009;Kroll 1981Kroll , 2007Jacomet, in press).…”
Section: Upgrading the Current State Of Knowledge Of Neolithic Crop Gmentioning
confidence: 91%
“…All these were regularly found in a carbonized state. If the waterlogged remains are considered, the importance of gathered plants for the wetland site economy is even more obvious; this may however be due to a better representation of most of the gathered plants when preservation is waterlogged (Cappers and Raemaekers 2008;Out 2008Out , 2009.…”
Section: The Environment During the Early And Middle Neolithic In Normentioning
confidence: 99%
“…Many Neolithic sites in south-west Asia, south-east Europe, and the central and south-west Mediterranean area have provided evidence for a wider range of cereals and pulses, whereas in central Europe, a narrower range of cereal crops is recorded, and pulses are usually restricted to pea and lentil (Bogaard, 2004;Colledge et al, 2005, 144;Kreuz et al, 2005;Out 2010). By the time farming reached Ireland and Britain, the range of cereal crops is further restricted, and evidence for any pulses is very poor.…”
Section: Comparison Of Irish Record With Evidence From Elsewhere In Ementioning
confidence: 99%
“…Burning of eutrophic wetland vegetation may have been related to management of natural vegetation (sensu Starr Carr in Mellars and Dark (1998); see also Bos et al 2007;Out 2009). Therefore, charred epidermis fragments of Poaceae and Cyperaceae were also recorded in the pollen slides (besides charcoal fragments originating from wood).…”
Section: Human Induced Fires or Natural Fires?mentioning
confidence: 99%
“…Fire ecology (the burning of vegetation in order to create open patches in the vegetation for non-agricultural reasons (Out 2009)) is a method of vegetation management often suggested to be practised, especially during the Mesolithic. For example, for the Starr Carr site in England, Mellars and Dark (1998) suggested that active burning of reed swamp was used to keep the occupation area largely free of reeds and other vegetation, and thus to maintain visibility and easy access to a lake.…”
Section: Human Induced Fires or Natural Fires?mentioning
confidence: 99%